Pengaruh Etika Bisnis Islami Terhadap Kinerja Pembiayaan Mudharabah Dengan Informasi Asimetri Sebagai Variabel Intervening Pada BMT Di Kabupaten Jember. - Hisamuddin, Nur; Ismira, Debby (BISNIS, 2015)
The title of this research the influence of Islamic Business Ethics of MudharabahFinancing performance with the Asymmetric Information as the Interveningvariable. The aim of the research to analyze the influence of Islamic businessethics to information asymmetry, the influence of Islamic business ethicsagainst the performance of mudharabah financing and analyzing the influenceof the asymmetry of information on the performance of the mudharabahfinancing. The location of the research on such as BMT in Jember districtusing quantitative research method, namely analysis of the band (PathAnalysis). research results meunjukkan that Islamic business ethics variable(dried shrimps) negative effect significantly against the asymmetric informationvariables (officers were present), Islamic business ethics variable turns tohave positive performance variable significantly mudharabah financing andthe asymmetric information variables (officers were present) negative effectsignificantly against the performance variable mudharabah financing (EPC)with a 0.085 and significant coefficient with the statistics of 10,401.